2013
DOI: 10.1073/pnas.1207586110
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 mutations rescue human tau-induced microtubule defects in Drosophila

Abstract: Neurons from the brains of Alzheimer's disease (AD) and related tauopathy patients contain neurofibrillary tangles composed of hyperphosphorylated tau protein. Tau normally stabilizes microtubules (MTs); however, tau hyperphosphorylation leads to loss of this function with consequent MT destabilization and neuronal dysfunction. Accordingly, MT-stabilizing drugs such as paclitaxel and epothilone D have been shown as possible therapies for AD and related tauopathies. However, MT-stabilizing drugs have common sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 51 publications
(64 reference statements)
8
83
0
1
Order By: Relevance
“…Histone deacetylase 6 (HDAC6) antagonizes Katanin 60 in regulating synaptic growth A previous study on cultured mammalian cells reported that acetylated MTs are favored for severing by katanin (Sudo and Baas, 2010 Xiong et al, 2013). We confirmed the effects of HDAC6 on the MT acetylation by western analysis (Fig.…”
Section: E) the Mejp Frequency In Katanin 60supporting
confidence: 76%
See 3 more Smart Citations
“…Histone deacetylase 6 (HDAC6) antagonizes Katanin 60 in regulating synaptic growth A previous study on cultured mammalian cells reported that acetylated MTs are favored for severing by katanin (Sudo and Baas, 2010 Xiong et al, 2013). We confirmed the effects of HDAC6 on the MT acetylation by western analysis (Fig.…”
Section: E) the Mejp Frequency In Katanin 60supporting
confidence: 76%
“…The spastin-null mutant spastin 5.75 was from N. Sherwood (Sherwood et al, 2004) and a UAS-spastin line was from K. Broadie (Trotta et al, 2004). The HDAC6 null mutant (HDAC6 KO ) and the UAS-HDAC6 line were from R. Jiao (Du et al, 2010), and two UAS lines expressing mutant HDAC6 with mutation H237A or H664A in the two deacetylase domains were described previously (Xiong et al, 2013). An RNAi line of Katanin 60 (v38369) was obtained from the Vienna Drosophila RNAi Center.…”
Section: Materials and Methods Drosophila Stocks And Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…8,15,16) Moreover, as Drosophila AD models show various and easily-quantifiable phenotypes, such as eye degeneration, developmental defects, shortened lifespan, locomotor defects, increased oxidative stress sensitivity, and learning and memory defects, they have been employed for finding genetic modifiers of AD-associated genes. [17][18][19][20][21][22][23] In addition, Drosophila AD models have been used to search and evaluate possible candidate drugs for AD.8) Recently, usage of Drosophila models has been extended to test the efficacy of traditional medicines, and successfully played a role in the analysis of their action mechanism at the molecular level.8) Our laboratory study revealed that SuHeXiang Wan, a traditional prescription, is neuroprotective against the cytotoxicity of Aβ42 by using Drosophila AD models. 24,25) …”
mentioning
confidence: 99%